Differential regulation of morphine antinociceptive effects by endogenous enkephalinergic system in the forebrain of mice - Sun Wei-Zen; Cheng Ying-Ying; Chen Tsung-Chieh; Shyu Bai-Chuang (SAGE Publishing, 2008)
Abstract Background Mice lacking the preproenkephalin (ppENK) gene are hyperalgesic and show more anxiety and aggression than wild-type (WT) mice. The marked behavioral changes in ppENK knock-out (KO) mice appeared to occur in supraspinal response to painful stimuli. However the functional role of enkephalins in the supraspinal nociceptive processing and their underlying mechanism is not clear. The aim of present study was to compare supraspinal nociceptive and morphine antinociceptive responses between WT and ppENK KO mice. Results The genotypes of bred KO mice were confirmed by PCR. Met-enkephalin immunoreactive neurons were labeled in the caudate-putamen, intermediated part of lateral septum, lateral globus pallidus, intermediated part of lateral septum, hypothalamus, and amygdala of WT mice. Met-enkephalin immunoreactive neurons were not found in the same brain areas in KO mice. Tail withdrawal and von Frey test results did not differ between WT and KO mice. KO mice had shorter latency to start paw licking than WT mice in the hot plate test. The maximal percent effect of morphine treatments (5 mg/kg and 10 mg/kg, i.p.) differed between WT and KO mice in hot plate test. The current source density (CSD) profiles evoked by peripheral noxious stimuli in the primary somatosenstory cortex (S1) and anterior cingulate cortex (ACC) were similar in WT and KO mice. After morphine injection, the amplitude of the laser-evoked sink currents was decreased in S1 while the amplitude of electrical-evoked sink currents was increased in the ACC. These differential morphine effects in S1 and ACC were enhanced in KO mice. Facilitation of synaptic currents in the ACC is mediated by GABA inhibitory interneurons in the local circuitry. Percent increases in opioid receptor binding in S1 and ACC were 5.1% and 5.8%, respectively. Conclusion The present results indicate that the endogenous enkephalin system is not involved in acute nociceptive transmission in the spinal cord, S1, and ACC. However, morphine preferentially suppressed supraspinal related nociceptive behavior in KO mice. This effect was reflected in the potentiated differential effects of morphine in the S1 and ACC in KO mice. This potentiation may be due to an up-regulation of opioid receptors. Thus these findings strongly suggest an antagonistic interaction between the endogenous enkephalinergic system and exogenous opioid analgesic actions in the supraspinal brain structures.